Optimalisasi Penggunaan Lahan dengan Sistem Agroforestri dan Pendampingan Pascapanennya di Kelompok Tani Dusun Kemuning, Gunungkidul - Ambar Kusumandari; Denny Irawati; Sri Astuti Soedjoko (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2015)
Kemuning sub village district is located in Bunder village, Patuk, Gunung Kidul. This area is near by the Bunder forest park and Wanagama Educational Forest. Most of the people live there are farmers. As the soil is relatively unfertile, they prefer to plant trees, so they called as forest community farmers. Among the trees, they plant cassava, peanut, and corn, so it called as agroforestry. In the field, the area seems still has the opportunity that can be added to be planted. Based on this situation, in this project, the optimalization of land use was introduced to ask the farmers to plant the undergrowth species includes: zingiber, kunyit and kencur. This project was started by introducing the agroforestry system, where they can plant together both trees and non trees at the same land. The socialization was done by inviting the farmers to come to the meeting. The advantages of agroforestry was explained to them, and also the post harvesting management to produce the instant zingiber was also trained and demonstrated to the female farmers. This product is also useful for attracting the local tourist who usually come at the week end. The output of this project was the agroforestry demplot can be built in the field, so the farmers can learn and study to develope at their own land. The female farmer can also make the instant zingiber as the healthy drink.